Android Implementation of Traditional Indonesia Fashion Application - Tukiyo, Tukiyo; Arifin, Ardian; Dewantara , Rizki; Ratnadewi, Ratnadewi; Anggraini, Julaiha Probo (Sinkron : jurnal dan penelitian teknik informatika, 2023)
Indonesia has been gifted with a wide range of diverse cultures from Sabang to Merauke, making Indonesia one of the biggest country with multi ethnic groups, races and cultures. Meanwhile, a lack of information that can be accessed by the students causing a big issue that needs to be addressed. The information of Indonesian traditional clothing is very limited, which has been represented as a characteristic of tribe and culture in each region and also used in the traditional ceremony. Therefore, this study aims to develop an Android-based educational game of traditional Indonesian clothing. The method used in this study was Research and Development approach. The results of this study showed that developing an educational game "Introduction to Traditional Clothing in Indonesia" on the Android platform,that provided information to users about any traditional musical instruments in Indonesia, helped students to recognize the particular culture through its traditional clothing as it could give an insight to them. From the results of testing carried out with the black box method, it could be concluded that this application enabled to function well and provide the beneficial information to user about the traditional clothing.